2020
DOI: 10.14419/ijet.v9i2.30270
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological empowerment and job satisfaction on turnover intentions directly and indirectly through affective commitment on registered nurses in healthcare industry of twin cities (Islamabad and Rawalpindi) of Pakistan

Abstract: The shift from financial capital to the human capital has brought a significant change in the workplace and market. The role of nurses is getting crucial day by day and there is great need of retention of nurses in order to sustain the smooth operation of hospitals. Nurses’ turnover has gained much importance and has become a concern for the hospitals. Psychological empowerment plays a vital role in retention of the employees and in return leads to success of the organization. Proper psychological empowerment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 130 publications
(182 reference statements)
0
6
0
Order By: Relevance
“…Therefore, there is a high level of stress. Because of this high level of stress, the lives and health of the employees are considerably impacted as well [ 14 , 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, there is a high level of stress. Because of this high level of stress, the lives and health of the employees are considerably impacted as well [ 14 , 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The included studies were conducted from 2001 to 2023. Four studies were from Canada [ 7 , 14 - 16 ], three from the United States [ 6 , 17 , 18 ], two studies from China [ 19 , 20 ], two from Turkey [ 21 , 22 ], and one each from South Korea [ 23 ], Malaysia and England [ 24 ], Sweden [ 25 ], Pakistan [ 26 ], Poland [ 27 ], Iraq [ 28 ], and Portugal [ 29 ]. The vast majority of studies used reliable and valid study tools, namely, the Psychological Empowerment Scale (PES) and the Job Satisfaction Scale (JSS) which showed a high Cronbach’s α coefficients.…”
Section: Reviewmentioning
confidence: 99%
“…[47][48][49] AC has been studied as a mediator in various research contexts, including its relationship with psychological empowerment, job satisfaction, and job stress. 11,50,51 Haque et al discovered that RL is linked to AC, 36 which in turn mediates the relationship between RL and employees' intention to quit their jobs. Afsar et al examined RL in relation to OC and found that RL has a significant positive impact on OC.…”
Section: Introductionmentioning
confidence: 99%